DIMENSIUNEA DE GEN ÎN DOMENIUL EDUCAŢIEI - USM ADMIN (Moldova State University, 2010)
Gender perspectives on education include the analysis of teaching in terms of gender, but also issues relating to gender awareness issues, initially induced by pre-university education system, and vocational education: gender exploration in educational practice, teaching strategies that provide equal learning opportunities for genders, cooperative learning and stimulating gender partnership etc.